A ranking of concurrent precipitation and wind events for the Iberian Peninsula. (17th September 2020) - Hénin, Riccardo; Ramos, Alexandre M.; Pinto, Joaquim G.; Liberato, Margarida L. R.
Abstract: The Iberian Peninsula (IP) is often affected by extreme precipitation and severe winds that are mostly associated with extratropical cyclones and their atmospheric fronts. ERA5 reanalysis data are used to revise and update two existing rankings of extreme precipitation and extreme potential wind‐loss days for the extended winter months on the IP. A ranking of concurrent precipitation and wind extreme events is produced by matching the two individual rankings for the IP and for specific IP subregions, including its main river basins. The intensity and the variability at the interannual and decadal scale are evaluated for precipitation, wind and concurrent precipitation and wind events. A systematic analysis of the underlying synoptic conditions is pursued for the top100 most extreme concurrent events including (a) cyclones' trajectories, (b) the presence of an Atmospheric River (AR), (c) recurrent patterns in the locations affected by precipitation and wind extremes and (d) possible long‐term trends. Results show that 85% of concurrent precipitation and wind extreme events are clearly associated with a cyclonic feature and most of these cyclones either cross the IP or pass to the northwest. Concurrent events are more likely occurring in the northwestern sectors of the IP on wintertime as in recent decades a downward trend for the events' frequency is observed in autumn. ARs are more likely associated with the strongest events occurring on the western sector of IP. Accordingly, the areas that mostly experience concurrent precipitation and wind extremes related to those systems are located in the northwestern sector of the peninsula. Abstract : In recent years, the study of concurrent weather events has become of great interest to the general public, stakeholders and scientists. Rankings of concurrent precipitation and wind events that affected the Iberian Peninsula and its main river basins over the period 1979–2018 are produced. The variability of the events is studied, and the underlying large‐scale synoptic conditions are examined. The associated cyclones are identified and classified according to their trajectories.